2018
DOI: 10.1007/s00145-018-9294-z
|View full text |Cite
|
Sign up to set email alerts
|

Koblitz Curves over Quadratic Fields

Abstract: where he suggested the possibility of defining anomalous elliptic curves over the base field F 4 . We present a careful implementation of the base and quadratic field arithmetic required for computing the scalar multiplication operation in such curves. We also introduce two ordinary Koblitz-like elliptic curves defined over F 4 that are equipped with efficient endomorphisms. To the best of our knowledge, these endomorphisms have not been reported before. In order to achieve a fast reduction procedure, we adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…Requires more cycle to perform operations [6,39] Requires less cycle to perform operations [6, 16] 2 Slower Multiplication [6] Faster multiplication [6, 58] 3 Higher power consumption [36] Lower power consumption [7, 36] 4 Cannot be implemented directly on the mobile phone [23,54] Can be implemented directly on the mobile phone. 5…”
Section: Resultsmentioning
confidence: 99%
“…Requires more cycle to perform operations [6,39] Requires less cycle to perform operations [6, 16] 2 Slower Multiplication [6] Faster multiplication [6, 58] 3 Higher power consumption [36] Lower power consumption [7, 36] 4 Cannot be implemented directly on the mobile phone [23,54] Can be implemented directly on the mobile phone. 5…”
Section: Resultsmentioning
confidence: 99%
“…We would like to remark that, although simple and perhaps even trivial in retrospect, the mentioned approaches for squaring have been proposed before in the literature. Precisely, [9] and [17] for the shuffle-based squaring and [35] for the CLMUL squaring.…”
Section: Binary Field Arithmeticmentioning
confidence: 99%
“…For the linear algebra task, Magma uses Lanczos' algorithm, with approximate running time L(s) ≈ d • (F (s) + ǫ) 2 where d denotes the per-row density of the matrix M . In fact, it can be shown that d ≤ g.…”
Section: Costs Of the Index-calculus Based Algorithmmentioning
confidence: 99%
“…Indeed, Pollard's Rho algorithm is the best known algorithm to solve DLP instances on a generic elliptic curve defined over a characteristic-two field of the form F q ℓ . This algorithm has an exponential computational complexity of (1 + o(1))O 1 2 π • q ℓ [1,2]. On the other hand, using an index-calculus strategy one can solve the DLP on the Jacobian of a curve H over F q with a subexponential complexity of L q g 1 2 , √ 2 + o(1) (as q and g tend to infinity).…”
Section: Introductionmentioning
confidence: 99%